2019
DOI: 10.1111/apm.12974
|View full text |Cite|
|
Sign up to set email alerts
|

Site‐specific absence of microfibrillar‐associated protein 4 (MFAP4) from the internal elastic membrane of arterioles in the rheumatoid arthritis synovial membrane: an immunohistochemical study in patients with advanced rheumatoid arthritis versus osteoarthritis

Abstract: Sorensen FB. Site-specific absence of microfibrillar-associated protein 4 (MFAP4) from the internal elastic membrane of arterioles in the rheumatoid arthritis synovial membrane: an immunohistochemical study in patients with advanced rheumatoid arthritis versus osteoarthritis. APMIS 2019;127:588-593.Microfibrillar-associated protein 4 (MFAP4) is a non-structural matrix protein with cell regulatory activities and a potential as seromarker for fibrosis. We aimed to study the occurrence of MFAP4 in the synovial me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In the tissue, it is detected in synovial sub-lining arteriole vessel walls and in adventitial tissue at sites of immune cell infiltration. However, it is absent from the internal elastic membrane of vessels in RA synovia, whilst present at high levels at this site in OA synovia 125 . The consequences of differential distribution of MFAP4 in OA and RA synovia are not yet clear, but these data highlight that alterations in local tissue architecture are not always reflected in 'bulk' serum or tissue analysis.…”
Section: Ra Diagnosis: the Truth Is In The Tissuementioning
confidence: 93%
“…In the tissue, it is detected in synovial sub-lining arteriole vessel walls and in adventitial tissue at sites of immune cell infiltration. However, it is absent from the internal elastic membrane of vessels in RA synovia, whilst present at high levels at this site in OA synovia 125 . The consequences of differential distribution of MFAP4 in OA and RA synovia are not yet clear, but these data highlight that alterations in local tissue architecture are not always reflected in 'bulk' serum or tissue analysis.…”
Section: Ra Diagnosis: the Truth Is In The Tissuementioning
confidence: 93%
“…MFAP4 is reported to be involved in ECM remodeling-associated diseases, such as vascular stenosis, 13 hepatic fibrosis, 25 and rheumatoid arthritis. 31 The pathophysiological characteristics of renal fibrosis and other fibrotic diseases are similar. Thus, we investigated the regulatory role of MFAP4 in renal fibrosis using MFAP4-deficient mice and TGF-β-treated HK-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Current research has shown that MFAP4 expression is correlated with numbers of functions, including coagulation, angiogenesis, tissue growth and remodeling and innate immunity [28][29][30]. Furthermore, increased MFAP4 protein play an extremely significant role in the development of fibrotic diseases, including heart, liver, joint and kidney fibrosis [10,13,14,16,25,31,32]. However, whether MFAP4 is related to OSF procedure has not been intensively investigated.…”
Section: Discussionmentioning
confidence: 99%